Development of Blended Activities to Promote Appreciation Value’s Folk tale for Youth: a case study of the "Khat Tha Na Khu Marn Allegory" in the murals at Phu Min temple, Nan Province - Boonyananta, Soamshine; Imsamraan , Suchart (DEC Journal : Art and Design, 2023)
Phumin Temple is a unique and famous temple in Nan Province. Inside, decorated a narrative mural called "Khat Tha Na Khu Marn" which has a wide variety of important values. However, the murals are still unknown and unappreciated by Nan province youths and residents. Therefore, this research intends to develop blended activities to promote appreciation values of "Khat Tha Na Khu Marn" narrative in the murals at Phu Min temple for youth. This research is divided into two phases: the blended activities development phase and the art activity prototype to promote appreciation values in the murals at Phu Min Temple, Nan Province Phase. The sample consisted of youths between the ages of 15 - 18 years old. The research instruments include a knowledge test, an appreciation test, an in-depth interview, and a blended activities satisfaction questionnaire. The results are as follows: Art activity "Legends in the Murals" consisted of 2 activities, which are learning the story of Khat Tha Na Khu Marn activity "Telling the Legends of Khat Tha Na Khu Marn" and learning the mural painting of Phumin temple activity "Enchanting Murals of Phumin Temple". The blended activities can be organized both on-site and online. The tryout results showed that the activities lead to higher mean scores on the knowledge test and Appreciation test compared to before the activities with the statistical significance level at .05. And they were satisfied with the activity set at a high level.